Enhanced Water Splitting Reaction Performance using TiO2 Deposited with Graphene Quantum Dots Grafted onto Gold Nanoparticles. Issue 33 (1st September 2021) - Sangkhun, Weradesh; Wanwong, Sompit; Wootthikanokkhan, Jatuphorn; Sinthiptharakoon, Kitiphat; Kumnorkaew, Pisist
Abstract: This study explores the feasibility of enhancing the water splitting performance of hybrid photo‐electrocatalyst made from graphene quantum dots (GQDs) grafted with gold nanoparticles (Au NPs) deposited on crystal facet engineered TiO2 (Ti). The effect of the Au NPs size on photoelectrochemical (PEC) water splitting performance was systematically investigated. It was found that the TiO2 with co‐exposed {001}‐{010} facet deposited with large particle size of Au NPs showed an enhancement in PEC performance, due to the localized surface plasmon resonance (LSPR). By contrast, the system containing Au NPs with smaller size retarded the transport rate of free electrons because of their high electron affinity. Interestingly, the hybrid catalyst (GQDs‐Aud40 /Ti) delivered a considerable high current density (0.535 mA/cm 2 at 1.23 V vs RHE), as compared to the pristine TiO2 (0.267 mA/cm 2 ). This was due to the capability of GQDs in acting as an electron extractor, withdrawing hot electrons produced by Au NPs and inhibiting the charge recombination. Overall, this work demonstrated that the PEC water splitting performance of TiO2 based photo‐electrocatalyst can be synergistically enhanced by combining the plasmonic effect of Au NPs and electron extractor properties of GQDs. Abstract : In this work, the composite photoanode made of GQDs, Aud40 NPs, and TiO2 {001}−{010} (GQDs‐Aud40 /Ti) gave the highest current density, owing to the synergistic effect between plasmon resonance of Au and charge separation of GQDs.